SOLIDARITAS TERHADAP ORANG-ORANG MISKIN DI ZAMAN INI - Dwi Putra N.S.A, Bonaventura; Borromeus Mulyatno, Carolus; Subali, Yohanes (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2024)
Living in diversity requires solidarity in fostering the potential of each element of national life and guarding against policies and actions that marginalize a group or an individual. The purpose of this study is to explore the thoughts of Y.B. Mangunwijaya and Pope Francis regarding solidarity with the poor to find important pillars of living together in diversity. The methods used in this research are literature study and comparative analysis. The ideas of the two figures are described and then comparatively analyzed to find important pillars of solidarity with the poor. The results of this study show that both figures have similar views on the understanding of solidarity based on faith motivation and responses to the context of community life. Solidarity is motivated by faith beliefs to serve the poor.Â  Solidarity is an act of care to help the poor, defend human dignity and realize social justice in the context of multireligious and multicultural society.